Efektifitas Penggunaan E-Modul Fisika Berbasis Kearifan Lokal Makanan Khas Kota Palembang Untuk Meningkatkan Keterampilan Kolaborasi Siswa SMA - Hartisyah Nadia; Ketang Wiyono; Ida Sriyanti (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the effect of the effectiveness of an e-module based on local food wisdom in the city of Palembang on the collaboration skills of high school students on temperature and heat material. This type of research is a quasi-experiment using the pretest-posttest method. The population of this study was class XI students of SMA Negeri 2 Palembang City. The data analysis technique uses quantitative data to analyze data collected from students' collaboration skill achievement scores. The results of data analysis show the average pretest on collaboration skills was 54. The average post-test score after implementing the e-module based on local food wisdom in Palembang on collaboration skills was 80. This shows that students' skills in collaboration skills have increased. after using e-modules based on local wisdom. The main finding of this research is that the application of an e-module based on local food wisdom in the city of Palembang is effective in improving students' collaboration skills. This is proven by the results of the N-gain test analysis showing that students with collaboration skills received a score of 0.72 in the high category.